Characteristics, significance and pathogenesis of atypical endometrial abnormalities associated with the presence of chorionic tissue - Arias Stella, Javier (2015)
The histological features of endometrial atypical alteration we have found in cases of uterine abortion, extópico pregnancy decribe, hydatidiform mole, choriocarcinoma, destruens chorioadenoma, syncytial endometry and normal uterine pregnancy, based on the study of 250 cases of uterine abortion, 44 cases of extópico pregnancy, 32 cases of hydatidiform mole, 25 cases of coriopitelioma, 6 cases of syncytial endometritis and 3 cases of apparently normal pregnancy.